The effects of elimination and non-elimination games on physical activity and psychosocial responses in children - Bruggeman, Karla E. (Kansas State University, 2008)
Physically active games are one way to increase caloric expenditure in children. It is unknown if the structure of physically active games impacts physical activity levels. Furthermore, there has been no research examining psychosocial responses during a single game session. This study examined the effects of elimination games (EG) and non-elimination games (NEG) on physical activity (PA), self-efficacy (SE), peer victimization (PV), and enjoyment in children. Children (n=29) in 4th-6th grade (65.5% male) participated in two sessions where they played either NEG or EG. Children were stratified according to gender and weight status into game sessions that were counter-balanced across two days. Each session consisted of playing two games 20 min. in duration. NEG were adopted from the evidence-based Coordinated Approach to Child Health (CATCH) games curriculum and modified for EG. Each child wore an Actigraph GT1M accelerometer and completed an 11-item questionnaire measuring self-efficacy, peer victimization, and enjoyment before and after each game session. Accelerometer data was analyzed using resting energy expenditure (METs). A mixed effects regression model was conducted with child and day nested within child as random effects and observation, game session, weight status, and gender as fixed effects. Overall, girls spent more time in sedentary PA compared to boys (p=0.0123). Children engaged in significantly more moderate-vigorous PA during NEG compared to EG (p=0.0013), ostensibly because of more time in moderate PA during NEG (p=0.0002) and less time in sedentary PA (p<0.0001). Furthermore, children significantly increased SE after playing both game sessions (p=0.0349), but a significant interaction between game session and time of measurement in the prediction of enjoyment showed that enjoyment increased after EG and decreased after NEG (p=0.0138). There were no differences in PV or weight status. These results provide preliminary evidence that NEG provide a greater amount of moderate-vigorous PA compared to EG and introduces differences in enjoyment responses during EG and NEG. Therefore, it is important to promote NEG to increase physical activity, but also important to monitor enjoyment responses to promote a healthy, but fun environment for children.
Keywords: children; physical activity; games; enjoyment; self-efficacy; elimination; Health Sciences, Public Health (0573)